Victimisation in correctional institutions of the Republic of Kazakhstan - Askarbekkyzy, А.; Tasybayeva, М.; Askarbekkyzy, Н. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The article is devoted to the study of the issues of victimisation of convicts in prisons. The article examines the main factors contributing to victimisation, such as social stigma, the influence of criminal subculture, inadequate protection of the rights of convicts, as well as problems of discrimination on ethnic and religious grounds. The author focuses on specific groups of prisoners most prone to victimisation, including young prisoners, minorities, persons with mental or physical disabilities and those convicted of sexual offences. Based on an analysis of risk factors, possible measures to reduce victimisation are suggested, such as raising standards of conditions of detention, providing accessible medical and psychological care, introducing social rehabilitation programmes, and raising the legal awareness of convicts. The article emphasises the need to revise penitentiary policy in order to create safe conditions for the successful adaptation of convicts to life at large after release.